9‐2: Optical Compensation Method for Wide Viewing Angle IPS LCD Using a Plastic Substrate. Issue 1 (May 2016) - Oka, Shinichiro; Sasaki, Toshinari; Tamaru, Takaya; Hyodo, Yosuke; Jin, Lu; Takayama, Shinichi; Komura, Shinichi
Abstract : The problem of a sheet LCD using plastic substrates is the narrow viewing angle of the large retardation of typical plastic materials. We have developed the optical compensation and a new process for plastic IPS‐LCD with wide viewing angle.